Tinjauan Komprehensif Manajemen Laba Kaitannya Dengan Agency Theory Dan Pengungkapan Informasi Keuangan - Jeanne Asteria Wawolangi (BIP's JURNAL BISNIS PERSPEKTIF, 2016)
Earnings management is a conflict of interest between the manager as agent and owner/shareholder as a principal. Where the impact of earnings management behavior will affect reported earnings. Earnings management conducted by the management to utilize accrual accounting policies do because of the uncertainty in the business competition which makes the company dealth with uncertainty fluctuations in earnings. This can lead to management efforts to manipulate reported earnings giving rise to information asymmetry. This is consistent with agency theory is the theory that focuses on the problems that arise between the principal-agent in the separation of ownership and control of the company. In this case due to the flexibility of management to manage the company resulted in the action management to maximize earnings for their own interests or the interests of the company. The results of this study indicate that earnings management and agency theory have interlocking relationships, where the agency problem arises when the principal difficulties to ensure that the agent acts to maximize the welfare of principal. While the disclosure of financial information is an important tool to address the agency problem between management and owners, because it is seen as an attempt to reduce information asymmetry.